Genetics of Tooth Size - Townsend Grant C. (Sciendo, 1978)
This paper summarises the findings of a genetic study of tooth size in a group of Australian Aboriginals. Measurements were obtained from a total of 392 dental casts collected as part of a longitudinal growth study of Aboriginals living at Yuendumu, a settlement town in the Northern Territory of Australia. Family data were compiled from genealogical records gathered over a number of years. The custom of polygyny practised by the Yuendumu people enabled the analysis of associations between both full-siblings and half-siblings.